Evaluating the Effectiveness of Consumer Protection Laws in Indonesia: A Case Study of E-Commerce - Puspitasari, Dara; Setjoatmadja, Sylvia (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2025)
This study evaluates the effectiveness of consumer protection laws in Indonesia's burgeoning e-commerce sector, focusing on the Consumer Protection Law No. 8 of 1999 and the Information and Electronic Transactions Law (UU ITE). Utilizing a normative legal research design with secondary data, the study examines the implementation of these laws and analyzes specific cases of consumer rights violations. Findings reveal significant challenges, including limited consumer awareness, inconsistent law enforcement across regions, and difficulties in regulating cross-border transactions. High-profile cases of fraud, counterfeit goods, and data breaches un-derscore the need for stronger enforcement mechanisms, enhanced consumer education, and updated legal frameworks to address the evolving digital landscape. The research concludes that while Indonesia has established a foundational legal structure for consumer protection, further improvements are necessary to ensure robust and effective safeguards in the e-commerce mar-ketplace. Recommendations include increased resources for regulatory bodies, comprehensive public awareness campaigns, and international cooperation to enhance the legal protection of consumers in the digital age. [Studi ini mengevaluasi efektivitas undang-undang perlindungan konsumen di sektor e-commerce yang sedang berkembang di Indonesia, dengan fokus pada Undang-Undang Perlindungan Konsumen No. 8 Tahun 1999 dan Undang-Undang Informasi dan Transaksi Elektronik (UU ITE). Memanfaatkan desain penelitian hukum normatif dengan data sekunder, penelitian ini mengkaji implementasi undang-undang tersebut dan menganalisis kasus-kasus spesifik pelanggaran hak konsumen. Temuan-temuan tersebut menunjukkan tantangan-tantangan yang signifikan, termasuk terbatasnya kesadaran konsumen, penegakan hukum yang tidak konsisten di seluruh wilayah, dan kesulitan dalam mengatur transaksi lintas batas. Kasus-kasus penipuan, barang palsu, dan pelanggaran data yang terkenal menggarisbawahi perlunya mekanisme penegakan hukum yang lebih kuat, peningkatan pendidikan konsumen, dan kerangka hukum yang diperbarui untuk mengatasi lanskap digital yang terus berkembang. Penelitian ini menyimpulkan bahwa meskipun Indonesia telah memiliki struktur hukum dasar untuk perlindungan konsumen, perbaikan lebih lanjut masih diperlukan untuk memastikan perlindungan yang kuat dan efektif di pasar e-commerce. Rekomendasinya mencakup peningkatan sumber daya bagi badan pengatur, kampanye kesadaran masyarakat yang komprehensif, dan kerja sama internasional untuk meningkatkan perlindungan hukum konsumen di era digital].